Comparing Cross-Sectoral Governance in Managing Post-Disaster in Indonesia - Achmad Nurmandi, Zuly Qodir, Eko Priyo Purnomo and Isnaini Muallidin (Social Science Research Network (SSRN), 2015)
The cross-sector governance or interorganizational network in the emergency and post disaster stage is new area of study in public administration. As a vulnerable state, Indonesia has been trying to set up a cross-sectoral governance in delaing with disaster since 2007. By reviewing the documentary data of previous disaster, we try to compare the cross sectoral governance in managing the disaster victims. We found that Indonesia government implemented cross sectoral disaster governance in Acheh, Merapi and Kelud Volcano, and Way Ela Dam burst. The different disaster were happened in al around Indonesia created the different new model cross sectoral governance.